Analyzing Effects on Average Execution time by varying Tasks and VMs on Cloud Data Centre - Chaturvedi, Amit; Rashid, Aaqib (International Journal of Computer Sciences and Engineering, 2025)
Cloud environment allows us to share the resources like CPU, Memory, etc to multiple tenants. These tenants put their tasks to the cloud server through the cloudlets. These cloudlets are treated as Process Elements (PEs). There are basically three entities Cloud Information Service [CIS], Data Centre, and Broker. All communications takes place between these three entities for executing the jobs or tasks. In this paper, we have created a cloud simulation environments, two sample sets are designed i.e. Table 1 and Table 2 to analyze the impacts of Submitted Tasks, Number of Virtual Machines variations on the Average Execution Time per task and illustrated through Figure 2 and Figure 3. It is observed that if the number of tasks and other environment constraints remains constant, increase in VMs decreases the Average Execution time per task, but limited number of VM can be increased according to the server architecture. If the number tasks are increased by keeping VMs and other simulation environments constant, the Average Execution time per task increases linearly.